Political Correctness and Its Relationships to Current Debates about Rights in the United States - Bouafia, Cherfi, Haithem Hafsa; Thamer, Safa (university of El-Oued, 2020)
Political Correctness comprises a large part of the American society; nevertheless, its juxtaposition with Freedom of Speech has been a source of huge concern. The relationship between the two elements and the encounters between their proponents produce distress on every occasion. Since Political Correctness is often separated from its earlier origins, the historical progress of this movement plays a significant part in the debates made about the issue. More importantly, Freedom of Speech, a principal which has emerged earlier, is of supreme importance. Its importance is nowadays compromised by refusal and obstruction of constructive discussions. Consequently, this study aims at defining Political Correctness in the twenty-first century and inspects the relationship it has with Freedom of Speech. The dissertation is a quantitative research based on the descriptive-analytical method and historical method. The study demonstrates the degree to which Political Correctness is unjustified. By evidence of its historical origins and progress, Political Correctness is analyzed on the ideological and historical levels with the university being the primary area of focus. Moreover, this claim is supported by empirical results and statistics that prove the dysfunctional nature of the movement and its failure in reaching its aims. يشكل التصحيح السياسي جزء كبيرا من المجتمع الأمريكي إلا أن مجاورتها لحرية التعبير مصدر قلق كبير إذ تسببت العلاقة بين هذين العنصرين والمناوشات التي تحدث بينهما في الكثير من التوتر في أكثر من مناسبة. بما أنه من الشائع فصل التصحيح السياسي عن أصله حيث يلعب التطور التاريخي لهذه الحركة دورا مهما في النقاشات المنعقدة حول الفضية. وبشكل أهم فإن حرين التعبير وهو مبدأ انبثق قبل التصحيح السياسي فائق الأهمية إلا أن هذه الأهمية مهددة بالخطر حاليا من خلال رفض وعرقلة الحوارات البناءة. لهذا تهدف هذه الدراسة إلى تعريف التصحيح السياسي في القرن الحادي والعشرون وبحث علاقتها حيث تكشف ، بحرية التعبير. إن هذه المذكرة بحث نوعي مبني على المنهجين الوصفي والتحليلي وكذا المنهج التاريخي حيث تم تحليلها على المستويين التاريخي والأيديولوجي ،الدراسة الدرجة التي أصبحت بها الصوابية السياسية أمرا غير مبرر والتركيز في ذلك على الجامعة استنادا للدلائل المتعلقة بالأصول التاريخية كما يؤيد هذا الإدعاء بإحصائيات ونتائج تجريبية من أجل إثبات الاختلال الوظيفي الذي تعاني منه هذه الحركة وفشلها في تحقيق أهدافها.
Keywords: American Society, Freedom of Speech, History, Juxtaposition, Ideology, Political Correctness; الإيديولوجية، التاريخ ، الجامعة، التجاور ،